Experience with the Applegate-Nelson-Metzenberg method of mutant enrichment in high sorbose medium - O. C. Yoder (Fungal Genetics Reports, 1979)
Experience with the Applegate-Nelson-Metzenberg method of mutant enrichment in high sorbose medium